School Counselors’ Meaning in Life as a Foundation for Professional Well-being and Professionalism: A Phenomenological Study - Arni Nur Laila; Nur Mega Aris Saputra; Nur Asiah (Bisma The Journal of Counseling, 2025)
The complex and demanding role of school counselors requires a strong sense of meaning in life (MIL). MIL plays a vital role in helping counselors manage stress, maintain psychological well-being, and strengthen their professional identity. Burnout and loss of purpose as counselors are complex issues in the professionalism of counselors. The purpose of this study is to explore the subjective, lived experiences of school counselors in finding and constructing MIL through their professional roles. The research employed a qualitative phenomenological approach. Data were collected through in-depth interviews and observations with five school counselors. Data analysis was conducted through three stages: reduction, reflection, and refinement. The findings reveal four key themes in the meaning in life of school counselors: (1) a sense of peace and fulfilment in performing their professional roles, (2) growing together with students, (3) the presence of support systems that sustain their career journey, and (4) spirituality that strengthens their professional commitment. These findings indicate that meaning in life serves as a psychological foundation that fosters emotional stability and professionalism among school counselors. When meaning in life is deeply internalized, school counselors naturally provide guidance and counseling services with sincerity, creativity, and empathy in supporting their students’ development.